A case of remission from pre-diabetes following intermittent hypoxic training. Issue 4 (July 2016) - Fuller, Nicholas R.; Courtney, Rosalba
Summary: A female patient (49 years of age) with obesity (body mass index: 35.3 kg/m 2 ) and diagnosed with pre-diabetes presented to the clinic of one of the authors (RC) with recent weight gain (approximately 10 kg) over the preceding 12 months, despite several unsuccessful attempts at weight loss. She reported being short of breath performing light activities and feeling fatigued the majority of the time. Treatment consisted of a run in period of five weeks following the Commonwealth Scientific and Industrial Research Organisation (CSIRO) diet, followed by four weeks of the CSIRO diet plus intermittent hypoxic training (IHT) using the GO2 ® altitude training device. Anthropometric measures, bloods and questionnaires were completed before treatment (week 0), end of diet phase (week 5), and end of diet plus IHT phase (week 9). At the end of week five, the patient had lost some weight and had an improvement in glycaemic control. However, there was a clinically greater improvement in weight loss and glycaemic control from week five to nine following the IHT, resulting in remission from pre-diabetes. This case study shows that incorporation of IHT has benefits existing beyond a standard dietary approach, helping to achieve remission from pre-diabetes back to a normal fasting glucose state.